Conductive polymer / metal oxide electrode surface modification material and preparation method thereof
By covering the polymer-metal complex layer on the surface of the positive electrode material of the lithium-ion battery, the problems of electrolyte corrosion and electrode internal resistance are solved, the structural stability and electrochemical performance of the battery are improved, and the service life of the battery is extended.
Patent Information
- Application Number
- CN202211720501.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-12-30
AI Technical Summary
During the use of lithium-ion batteries, due to the decomposition of the electrolyte, the positive electrode material is corroded, the transition metal precipitation, the structure is damaged, resulting in the battery capacity attenuation and service life. The existing surface coating is too thick and will hinder the ions. and electron transmission, increasing electrode internal resistance.
The surface modification material of the conductive polymer/metal oxide electrode covering the surface of the metal oxide nanoparticles is used to form a polymer-metal complex layer through complexing reaction, and metal ions are transferred as electrons. Channels, reduce interface resistance, increase charge transfer rate, and provide mechanical strength.
Effectively inhibit the accumulation of hydrogen fluoride, reduce the precipitation of transition metals, improve the stability and cycle life of the electrode structure, significantly improve the electrochemical performance and use stability, and reduce the resistance of the electrode.
Smart Images

Figure CN116072869B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery electrode materials, and in particular to a conductive polymer / metal oxide electrode surface modification material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy storage density, large capacity, no memory effect, high rated voltage, low self-discharge rate, light weight, long service life, strong adaptability to high and low temperatures, and green environmental protection, and are widely used in people's daily lives. As the core component of lithium-ion batteries, the positive electrode plays an important role in the charging and discharging process of lithium batteries. The stability and specific capacity of the positive electrode material determine the overall performance of the lithium battery. However, during the use of lithium-ion batteries, the electrolyte will decompose to produce by-products such as hydrogen fluoride, which will lead to corrosion of the positive electrode material and precipitation of transition metals, thereby destroying the structure of the positive electrode material, causing the battery capacity to decay and the service life to be reduced.
[0003] Surface coating is one of the effective methods to improve the structural stability of positive electrode materials. It not only protects positive electrode materials from electrolyte corrosion, but also provides them with new physical and chemical properties and higher mechanical strength. 2 O 3 Metal oxides such as fluorine can react with trace amounts of hydrogen fluoride in the electrolyte to neutralize it, inhibiting the corrosion of hydrogen fluoride to the electrode and further catalytic decomposition of the electrolyte, effectively improving the stability of the lithium battery. However, too thick a coating will hinder the transmission of ions and electrons; and the thin coating preparation process is more demanding and it is difficult to achieve the expected protection effect. Therefore, how to provide coating protection for the positive electrode material while minimizing the internal resistance caused by the coating is the key to further improving the performance of lithium-ion batteries. Summary of the invention
[0004] In view of this, the present invention provides a conductive polymer / metal oxide electrode surface modification material and a preparation method thereof, which can provide stable mechanical properties, accelerate the charge transfer rate, effectively reduce the resistance of the electrode, and improve the electrochemical properties and use stability of lithium-ion batteries.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] A conductive polymer / metal oxide electrode surface modification material, comprising metal oxide nanoparticles and a polymer-metal complex layer coated on the surface of the metal oxide nanoparticles, wherein the polymer-metal complex layer accounts for 0.1% to 20% of the total mass of the surface modification material; the metal oxide nanoparticles are Al 2 O 3 、ZrO2 , MgO or TiO 2 At least one of the following: the polymer-metal complex layer is formed by complexing a polymer containing an electron-donating group with a metal ion.
[0007] In order to solve the problem of increased internal resistance of the electrode due to excessively thick coating on the surface of the electrode, the inventors adopted the method of coating the surface of the metal oxide with a conductive material to improve the conductive properties of the material. However, the inventors found that common conductive materials such as carbon nanotubes, graphene and other graphite materials have a large size (diameter of several microns), and the modification effect on nano-scale metal oxides is not ideal, and the electrochemical properties of the electrode materials cannot be effectively improved; while conductive polymer materials such as polyacetylene, polyparaphenylene, polypyrrole and polythiophene, due to their high crystallinity, generally have the characteristics of insolubility and infusibility, making the processing process extremely difficult and difficult to be widely used. The inventors have conducted a lot of research and found that by coating metal oxide nanoparticles with products formed by complexing polymers containing electron-donating groups with metal ions, the problem of increased internal resistance due to excessively thick coating can be effectively solved. In the formed polymer-metal complex, metal ions can act as electron transfer channels, effectively reduce interface resistance, and ensure the effective transfer of electrons during rapid charge and discharge, while polymers can provide stable mechanical properties and improve the safety performance of batteries.
[0008] Compared with the prior art, the conductive polymer / metal oxide electrode surface modification material provided by the present invention is coated with a polymer-metal complex layer of a specific proportion on the surface of metal oxide nanoparticles. On the one hand, the modification material can coat the positive electrode material of the battery, thereby hindering the direct contact between the electrode and the electrolyte, effectively inhibiting the accumulation of hydrogen fluoride during the cycle, reducing the precipitation of transition metals and the formation of cycle electrode cracks, and improving the structural stability and cycle life of the lithium ion battery; on the other hand, the polymer-metal complex coated on the surface of the modification material can accelerate the charge transfer rate of the material and effectively reduce the resistance of the electrode. The above two aspects work synergistically to significantly improve the electrochemical performance and use stability of the electrode material.
[0009] Optionally, in the polymer-metal complex layer, the mass of the metal ions accounts for 1% to 40% of the mass of the polymer-metal complex. When the mass of the metal ions and the polymer is within a specific range, the formed polymer-metal complex can maintain a stable structure, and while ensuring the electronic conduction efficiency, the metal ions will not be deintercalated. This can improve the structural stability, cycle life and conductivity of the prepared electrode.
[0010] Optionally, the number average molecular weight of the polymer is 2000Da to 100000Da.
[0011] Optionally, the electron donating group is at least one of an amino group, a carboxyl group, a hydroxyl group or a thiol group.
[0012] Optionally, the metal ion is Zn 2+ , Mn 2+ Mg 2+ , Cu 2+ 、Ni 3+ , Fe 3+ , Li 1+ or Al 3+ The metal ions are obtained by dissolving soluble metal salts.
[0013] Optionally, the polymer is polyethyleneimine, polyvinyl alcohol, sulfonated polyethersulfone, hyperbranched polyglycerol, polyethylene glycol, polyacrylic acid or polythiol.
[0014] Optionally, the metal ions are derived from soluble metal salts.
[0015] Optionally, the particle size distribution of the metal oxide nanoparticles is: D10 ≥ 30 nm, 100 nm ≤ D50 ≤ 300 nm, D90 ≤ 900 nm; and the thickness of the polymer-metal complex layer is 10 nm to 50 nm.
[0016] The present invention also provides a method for preparing a conductive polymer / metal oxide electrode surface modification material, comprising the following steps:
[0017] Step a, mixing the metal oxide and the first dispersion, grinding, and drying to obtain metal oxide nanoparticles;
[0018] Step b, adding the polymer and the metal oxide nanoparticles into the second dispersion, mixing them evenly at 45°C to 80°C, then adding a soluble metal salt, carrying out a complexation reaction at 45°C to 80°C, washing and drying after the reaction is completed, to obtain the conductive polymer / metal oxide electrode surface modification material.
[0019] Compared with the prior art, the preparation method of the conductive polymer / metal oxide electrode surface modification material provided by the present invention forms a polymer-metal complex by in-situ polymerization on the surface of metal oxide nanoparticles, so that electrons can be transferred between metal ions, thereby improving the conductivity of the modified material; at the same time, the in-situ coated polymer-metal complex can also significantly improve the structural stability of the electrode material, effectively avoiding the corrosion of the electrode by byproducts such as hydrogen fluoride during the charge and discharge process, thereby improving the cycle stability of the battery. The preparation method provided by the present invention is simple, the raw materials are easy to obtain, and the prepared electrode surface modification material can improve the structural stability and electrochemical performance of the positive electrode material, and has broad application prospects in the field of lithium ion battery electrode materials.
[0020] Optionally, in step a, the first dispersion liquid is water, ethanol, acetamide, acetone or methyl pyrrolidone.
[0021] Optionally, in step b, the second dispersion liquid is water, ethanol, acetamide, acetone or methyl pyrrolidone.
[0022] Optionally, in step a, the mass ratio of the metal oxide to the first dispersion is 1-5:5-9.
[0023] Optionally, in step a, the particle size distribution of the metal oxide nanoparticles obtained by grinding is: D10 ≥ 30 nm, 100 nm ≤ D50 ≤ 300 nm, and D90 ≤ 900 nm.
[0024] Optionally, in step b, the mass ratio of the metal oxide nanoparticles to the second dispersion is 1-5:5-9.
[0025] Optionally, in step b, the mass ratio of the polymer, the metal oxide nanoparticles and the soluble metal salt is 0.001-0.2:1:0.001-0.08.
[0026] The addition amounts of the preferred polymer, metal oxide nanoparticles and soluble metal salts can enable the prepared conductive polymer / metal oxide electrode surface modification material to provide more electron transport channels, effectively reduce the interface resistance on the surface of the positive electrode material, increase the electron transfer rate, and enable the lithium ion battery electrode to exhibit more excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The cycle performance diagram of the battery prepared by using the conductive polymer / metal oxide electrode surface modification material prepared in Example 1 of the present invention;
[0028] Figure 2 The cycle performance diagram of the battery prepared by using the conductive polymer / metal oxide electrode surface modification material prepared in Example 2 of the present invention;
[0029] Figure 3 This is a cycle performance diagram of a battery made using the conductive polymer / metal oxide electrode surface modification material prepared in Example 3 of the present invention;
[0030] Figure 4 This is a cycle performance diagram of a battery made using the metal oxide nanoparticles prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] In order to better illustrate the present invention, further examples are given below.
[0033] Example 1
[0034] The present invention provides a method for preparing a conductive polymer / metal oxide electrode surface modification material, comprising the following steps:
[0035] Step a: 300 kg of α-Al 2 O 3 Add to 1000 kg of water, grind the mixture in a ball mill to a particle size distribution of: D10 is 34 nm, D50 is 151 nm, D90 is 472 nm, and spray-dry to obtain metal oxide nanoparticles. The particle size distribution test method of this embodiment is the light scattering method.
[0036] Step b: prepare 1000 kg of an aqueous solution containing 2% by mass of polyvinyl alcohol, disperse 300 kg of the above-mentioned metal oxide nanoparticles therein, stir thoroughly at 50° C. for 1 hour to make them completely dispersed and uniform, then add 20 kg of aluminum chloride, maintain the temperature, and continue stirring for 30 minutes until they are fully mixed and uniform, separate the obtained product, wash it thoroughly with pure water, and then spray dry it to obtain a conductive polymer / metal oxide electrode surface modification material.
[0037] The particle size of the surface modification material of the electropolymer / metal oxide electrode was determined by light scattering, and it was calculated that a polymer-metal complex layer with a thickness of 10 nm to 50 nm was formed on the surface of the metal oxide nanoparticles.
[0038] The positive electrode material of a lithium-ion battery is modified by using the conductive polymer / metal oxide electrode surface modification material prepared above, and the specific steps are as follows:
[0039] S1, weighing the lithium-ion battery positive electrode material NCM811 and the conductive polymer / metal oxide electrode surface modification material prepared above, placing them in a high-speed mixer at a mass ratio of 1000:1 and mixing them evenly to obtain a material.
[0040] S2, placing the above materials in a high temperature reaction furnace for calcining at a temperature of 200° C. for a sintering time of 12 hours to obtain a modified lithium ion battery positive electrode material.
[0041] Example 2
[0042] The present invention provides a method for preparing a conductive polymer / metal oxide electrode surface modification material, comprising the following steps:
[0043] Step a: 300 kg of α-Al 2 O 3 Add to 1000 kg of water, grind the mixture in a ball mill to a particle size distribution of: D10 is 44 nm, D50 is 145 nm, D90 is 376 nm, and spray-dry to obtain metal oxide nanoparticles. The particle size distribution test method of this embodiment is the light scattering method.
[0044] Step b: prepare 1000 kg of an alcohol solution containing 2% by mass of polyacrylic acid, disperse 200 kg of the above-mentioned metal oxide nanoparticles therein, stir thoroughly for 1 hour at 45° C. to make them completely dispersed and uniform, then add 8 kg of magnesium chloride, maintain the temperature, and continue stirring for 30 minutes until they are fully mixed and uniform, separate the obtained product, wash it thoroughly with pure water, and then spray dry it to obtain a conductive polymer / metal oxide electrode surface modification material.
[0045] The particle size of the surface modification material of the electropolymer / metal oxide electrode was determined by light scattering, and it was calculated that a polymer-metal complex layer with a thickness of 10 nm to 50 nm was formed on the surface of the metal oxide nanoparticles.
[0046] The positive electrode material of a lithium-ion battery is modified by using the conductive polymer / metal oxide electrode surface modification material prepared above, and the specific steps are as follows:
[0047] S1, weighing the lithium-ion battery positive electrode material NCM811 and the conductive polymer / metal oxide electrode surface modification material prepared above, placing them in a high-speed mixer at a mass ratio of 1000:1 and mixing them evenly to obtain a material.
[0048] S2, placing the above materials in a high temperature reaction furnace for calcining at a temperature of 200° C. for a sintering time of 12 hours to obtain a modified lithium ion battery positive electrode material.
[0049] Example 3
[0050] The present invention provides a method for preparing a conductive polymer / metal oxide electrode surface modification material, comprising the following steps:
[0051] Step a: 300 kg of α-Al 2 O 3 and 80kg of γ-Al 2 O 3Add to 1000 kg of water, grind the mixture in a ball mill to a particle size distribution of: D10 is 57 nm, D50 is 159 nm, D90 is 384 nm, and spray-dry to obtain metal oxide nanoparticles. The particle size distribution test method of this embodiment is the light scattering method.
[0052] Step b: prepare 1000 kg of an aqueous solution containing 2% by mass of polyethyleneimine, disperse 260 kg of the above-mentioned metal oxide nanoparticles therein, stir thoroughly at 60° C. for 1 hour to make them completely dispersed and uniform, then add 2 kg of cupric chloride, continue stirring at 70° C. for 30 minutes until they are fully mixed and uniform, separate the obtained product, wash it thoroughly with pure water, and then spray dry it to obtain a conductive polymer / metal oxide electrode surface modification material.
[0053] The particle size of the surface modification material of the electropolymer / metal oxide electrode was determined by light scattering, and it was calculated that a polymer-metal complex layer with a thickness of 10 nm to 50 nm was formed on the surface of the metal oxide nanoparticles.
[0054] The positive electrode material of a lithium-ion battery is modified by using the conductive polymer / metal oxide electrode surface modification material prepared above, and the specific steps are as follows:
[0055] S1, weighing the lithium-ion battery positive electrode material NCM811 and the conductive polymer / metal oxide electrode surface modification material prepared above, placing them in a high-speed mixer at a mass ratio of 1000:1 and mixing them evenly to obtain a material.
[0056] S2, placing the above materials in a high temperature reaction furnace for calcining at a temperature of 200° C. for a sintering time of 12 hours to obtain a modified lithium ion battery positive electrode material.
[0057] Example 4
[0058] The present invention provides a method for preparing a conductive polymer / metal oxide electrode surface modification material, comprising the following steps:
[0059] Step a: 300 kg MgO is added to 1000 kg water, the mixture is ground in a ball mill to a particle size distribution of: D10 is 51 nm, D50 is 262 nm, D90 is 593 nm, and the mixture is spray-dried to obtain metal oxide nanoparticles. The particle size distribution test method of this embodiment is a light scattering method.
[0060] Step b: prepare 1000 kg of acetamide solution containing 2% by mass of sulfonated polyethersulfone, disperse 180 kg of the above-mentioned metal oxide nanoparticles therein, stir thoroughly at 70° C. for 1 hour to make them completely dispersed and uniform, then add 4.2 kg of zinc chloride, continue stirring at 60° C. for 30 minutes until they are fully mixed and uniform, separate the obtained product, wash it thoroughly with pure water and then spray dry it to obtain a conductive polymer / metal oxide electrode surface modification material.
[0061] The particle size of the surface modification material of the electropolymer / metal oxide electrode was determined by light scattering, and it was calculated that a polymer-metal complex layer with a thickness of 10 nm to 50 nm was formed on the surface of the metal oxide nanoparticles.
[0062] The positive electrode material of a lithium-ion battery is modified by using the conductive polymer / metal oxide electrode surface modification material prepared above, and the specific steps are as follows:
[0063] S1, weighing the lithium-ion battery positive electrode material NCM811 and the conductive polymer / metal oxide electrode surface modification material prepared above, placing them in a high-speed mixer at a mass ratio of 1000:1 and mixing them evenly to obtain a material.
[0064] S2, placing the above materials in a high temperature reaction furnace for calcining at a temperature of 200° C. for a sintering time of 12 hours to obtain a modified lithium ion battery positive electrode material.
[0065] Example 5
[0066] The present invention provides a method for preparing a conductive polymer / metal oxide electrode surface modification material, comprising the following steps:
[0067] Step a: 300 kg of ZrO 2 Add to 1000 kg of water, grind the mixture in a ball mill to a particle size distribution of: D10 is 53 nm, D50 is 258 nm, D90 is 586 nm, and spray-dry to obtain metal oxide nanoparticles. The particle size distribution test method of this embodiment is the light scattering method.
[0068] Step b, preparing 1000 kg of an aqueous solution containing 2% by mass of hyperbranched polyglycerol, dispersing 180 kg of the above-mentioned metal oxide nanoparticles therein, stirring at 80° C. for 1 hour to make them completely dispersed and uniform, then adding 7 kg of ferric chloride, maintaining the temperature, and continuing to stir for 30 minutes until fully mixed and uniform, separating the obtained product, washing it with pure water, and then spray drying it to obtain a conductive polymer / metal oxide electrode surface modification material.
[0069] The particle size of the surface modification material of the electropolymer / metal oxide electrode was determined by light scattering, and it was calculated that a polymer-metal complex layer with a thickness of 10 nm to 50 nm was formed on the surface of the metal oxide nanoparticles.
[0070] The positive electrode material of a lithium-ion battery is modified by using the conductive polymer / metal oxide electrode surface modification material prepared above, and the specific steps are as follows:
[0071] S1, weighing the lithium-ion battery positive electrode material NCM811 and the conductive polymer / metal oxide electrode surface modification material prepared above, placing them in a high-speed mixer at a mass ratio of 1000:1 and mixing them evenly to obtain a material.
[0072] S2, placing the above materials in a high temperature reaction furnace for calcining at a temperature of 200° C. for a sintering time of 12 hours to obtain a modified lithium ion battery positive electrode material.
[0073] Example 6
[0074] The present invention provides a method for preparing a conductive polymer / metal oxide electrode surface modification material, comprising the following steps:
[0075] Step a: 300 kg of α-Al 2 O 3 and 80kg of γ-Al 2 O 3 Add to 1000 kg of water, grind the mixture in a ball mill to a particle size distribution of: D10 is 56 nm, D50 is 149 nm, D90 is 284 nm, and spray-dry to obtain metal oxide nanoparticles. The particle size distribution test method of this embodiment is the light scattering method.
[0076] Step b, preparing 1000 kg of an aqueous solution containing 3% by mass of polyethylene glycol, dispersing 180 kg of the above-mentioned metal oxide nanoparticles therein, stirring at 60° C. for 1 h to make them completely dispersed, then adding 5 kg of lithium chloride, maintaining the temperature, and continuing to stir for 30 min until fully mixed, separating the obtained product, washing it with pure water, and then spray drying it to obtain a conductive polymer / metal oxide electrode surface modification material.
[0077] The particle size of the surface modification material of the electropolymer / metal oxide electrode was determined by light scattering, and it was calculated that a polymer-metal complex layer with a thickness of 10 nm to 50 nm was formed on the surface of the metal oxide nanoparticles.
[0078] The positive electrode material of a lithium-ion battery is modified by using the conductive polymer / metal oxide electrode surface modification material prepared above, and the specific steps are as follows:
[0079] S1, weighing the lithium-ion battery positive electrode material NCM811 and the conductive polymer / metal oxide electrode surface modification material prepared above, placing them in a high-speed mixer at a mass ratio of 1000:1 and mixing them evenly to obtain a material.
[0080] S2, placing the above materials in a high temperature reaction furnace for calcining at a temperature of 200° C. for a sintering time of 12 hours to obtain a modified lithium ion battery positive electrode material.
[0081] Comparative Example 1
[0082] This comparative example provides a method for preparing a conductive polymer / metal oxide electrode surface modification material, comprising the following steps:
[0083] 300 kg of α-Al 2 O 3 The mixture was added into 1000 kg of water, and ground in a ball mill to a particle size distribution of: D10 is 31 nm, D50 is 153 nm, and D90 is 461 nm. The mixture was spray-dried to obtain metal oxide nanoparticles.
[0084] The metal oxide nanoparticles prepared above are used to modify the positive electrode material of the lithium-ion battery. The specific steps are as follows:
[0085] S1, weighing lithium-ion battery positive electrode material NCM811 and the metal oxide nanoparticles prepared above, placing them in a high-speed mixer at a mass ratio of 1000:1 and mixing them evenly to obtain a material.
[0086] S2, placing the above materials in a high temperature reaction furnace for calcining at a temperature of 200° C. for a sintering time of 12 hours to obtain a modified lithium ion battery positive electrode material.
[0087] In order to better illustrate the characteristics of the conductive polymer / metal oxide electrode surface modification material provided by the embodiments of the present invention, the modified lithium ion battery positive electrode materials prepared in Examples 1 to 3 and Comparative Example 1 are made into LIR2032 button batteries for performance testing.
[0088] The battery prepared above was subjected to a long cycle charge and discharge test on a battery tester. The test temperature was 25°C, the discharge rate was 0.5C, and the test voltage range was 3.0V to 4.25V. The cycle performance test results are shown in Figures 1 to 4 As shown in the figure, it can be seen that the battery made of the lithium-ion battery material modified by Examples 1 to 3 of the present invention has a high cycle retention rate, and the battery capacity has no obvious change after 50 cycles, and has stable cycle performance, while the battery made by Comparative Example 1 decays faster.
[0089] The battery capacity of the prepared battery was tested at discharge rates of 0.1C, 1C and 10C respectively. The test results are shown in Table 1.
[0090] Table 1 Changes in battery capacity at different discharge rates
[0091] Discharge rate 0.1C 1C 10C Example 1 100% 96.5% 75.6% Example 2 100% 96.4% 75.5% Example 3 100% 96.6% 75.8% Comparative Example 1 100% 92.1% 65.5%
[0092] It can be seen from the above table that the batteries made of the lithium-ion battery materials modified by Examples 1 to 3 can maintain a higher battery capacity under high-rate discharge conditions compared to the batteries made in Comparative Example 1. In particular, under a discharge rate of 10C, the electrodes modified with the conductive polymer / metal oxide electrode surface modification material provided by the present invention can maintain a battery capacity of more than 75.5%; while the electrodes modified only by metal oxides in Comparative Example 1 suffer serious battery capacity loss. This experimental result shows that the conductive polymer / metal oxide electrode surface modification material provided by the present invention can improve the conductivity of the material, so that the modified electrode material can maintain a more stable property during long-term charge and discharge, especially under high-rate charge and discharge conditions, thereby maintaining a higher battery capacity.
[0093] In summary, the conductive polymer / metal oxide electrode surface modification material prepared in the embodiment of the present invention effectively improves the electrochemical performance and stability of the electrode material by coating a specific proportion of polymer-metal complex on the surface of metal oxide nanoparticles.
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A conductive polymer / metal oxide electrode surface modification material, characterized in that: It comprises metal oxide nanoparticles and a polymer-metal complex layer coated on the surface of the metal oxide nanoparticles, wherein the polymer-metal complex layer accounts for 0.1% to 20% of the total mass of the surface modification material; The metal oxide nanoparticles are at least one of Al2O3, ZrO2, MgO or TiO2; The polymer-metal complex layer is formed by complexing a polymer containing an electron-donating group with a metal ion, wherein the mass of the metal ion accounts for 1% to 40% of the mass of the polymer-metal complex; The method for preparing the conductive polymer / metal oxide electrode surface modification material comprises the following steps: Step a, mixing the metal oxide and the first dispersion, grinding, and drying to obtain metal oxide nanoparticles; Step b, adding the polymer and the metal oxide nanoparticles into the second dispersion, mixing them evenly at 45°C-80°C, then adding a soluble metal salt, carrying out a complexation reaction at 45°C-80°C, washing and drying after the reaction is completed, to obtain the conductive polymer / metal oxide electrode surface modification material.
2. The conductive polymer / metal oxide electrode surface modification material according to claim 1, characterized in that: The number average molecular weight of the polymer is 2000Da~100000Da; The electron donating group is at least one of an amino group, a carboxyl group, a hydroxyl group or a thiol group; The metal ion is Zn 2+ , Mn 2+ Mg 2+ , Cu 2+ 、Ni 3+ , Fe 3+ , Li + or Al 3+ At least one of .
3. The conductive polymer / metal oxide electrode surface modification material according to claim 1 or 2, characterized in that: The polymer is polyethyleneimine, polyvinyl alcohol, sulfonated polyethersulfone, hyperbranched polyglycerol, polyethylene glycol, polyacrylic acid or polythiol.
4. The conductive polymer / metal oxide electrode surface modification material according to claim 1, characterized in that: The particle size distribution of the metal oxide nanoparticles is: D10 ≥ 30 nm, 100 nm ≤ D50 ≤ 300 nm, D90 ≤ 900 nm; The thickness of the polymer-metal complex layer is 10 nm to 50 nm.
5. The conductive polymer / metal oxide electrode surface modification material according to claim 1, characterized in that: In step a, the first dispersion liquid is water, ethanol, acetamide, acetone or methyl pyrrolidone; and / or In step b, the second dispersion liquid is water, ethanol, acetamide, acetone or methyl pyrrolidone.
6. The conductive polymer / metal oxide electrode surface modification material according to claim 1, characterized in that: In step a, the mass ratio of the metal oxide to the first dispersion is 1-5:5-9.
7. The conductive polymer / metal oxide electrode surface modification material according to claim 1, characterized in that: In step b, the mass ratio of the metal oxide nanoparticles to the second dispersion is 1-5:5-9; and / or In step b, the mass ratio of the polymer, the metal oxide nanoparticles and the soluble metal salt is 0.001-0.2:1:0.001-0.08.
